2001
DOI: 10.1136/oem.58.8.511
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particles and nitrogen oxides generated by gas and electric cooking

Abstract: Objectives-To measure the concentrations of particles less than 100 nm diameter and of oxides of nitrogen generated by cooking with gas and electricity, to comment on possible hazards to health in poorly ventilated kitchens. Methods-Experiments with gas and electric rings, grills, and ovens were used to compare diVerent cooking procedures. Nitrogen oxides (NO x ) were measured by a chemiluminescent ML9841A NO x analyser. A TSI 3934 scanning mobility particle sizer was used to measure average number concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
190
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(204 citation statements)
references
References 45 publications
(22 reference statements)
11
190
1
2
Order By: Relevance
“…Furthermore, it should be stated that the Dust Trak employed in this investigation does not provide ideal measures of particulate matter exposures, and may overestimate exposures determined by reference gravimetric methods (Jenkins et al, 2004). The identification of electric oven use and cigarette smoking as significant predictors of mean indoor UFP exposures in this study is consistent with previous studies which have shown these to be strong sources of indoor UFPs (Dennekamp et al, 2001;Afshari et al, 2005). Likewise, the observed pattern of increased indoor UFPs during the evening relative to overnight hours has also been reported previously (Abt et al, 2000;, and supports the role of cooking as an important source of indoor UFPs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, it should be stated that the Dust Trak employed in this investigation does not provide ideal measures of particulate matter exposures, and may overestimate exposures determined by reference gravimetric methods (Jenkins et al, 2004). The identification of electric oven use and cigarette smoking as significant predictors of mean indoor UFP exposures in this study is consistent with previous studies which have shown these to be strong sources of indoor UFPs (Dennekamp et al, 2001;Afshari et al, 2005). Likewise, the observed pattern of increased indoor UFPs during the evening relative to overnight hours has also been reported previously (Abt et al, 2000;, and supports the role of cooking as an important source of indoor UFPs.…”
Section: Discussionsupporting
confidence: 85%
“…Indoor sources of UFPs have been investigated in a number of studies, and include cooking systems, portable heaters, burning candles, tobacco smoke, natural gas clothes dryers, and others (Li et al, 1993;Abt et al, 2000;Wallace, 2000;Dennekamp et al, 2001;Morawska et al, 2003;He et al, 2004;Wallace et al, 2004;Afshari et al, 2005;Hussein et al, 2005;Matson, 2005;Wallace, 2005). However, studies to date have generally been conducted in 15 or fewer homes and have not compared indoor UFP exposures according to the type of home heating system.…”
Section: Introductionmentioning
confidence: 99%
“…However, indoor sources of NO 2 exposure, such as cooking with gas or the use of a gas heater, can contribute to personal NO 2 exposure and confound the observed association between personal NO 2 exposure level and traffic-related factors (Kodama et al 2002;Dennekamp et al 2001). After adjusting for heat source or cooking source in the present study, we found less significant difference in personal exposure level to NO 2 between categories of traffic-related factors compared to the model without adjustment.…”
Section: Discussioncontrasting
confidence: 34%
“…Outdoor UFP concentrations were measured for 1-2 years in several US cities (U.S. EPA Supersites program; Solomon et al, 2008), and near roadways in California (Zhu et al, 2002) and also in Erfurt and Augsberg, Germany (Wichmann et al, 2000). Residential indoor concentrations have also been reported (Abt et al, 2000;Dennekamp et al, 2001;Long et al, 2001;Wallace and Howard-Reed, 2002;Klepeis et al, 2003;He et al, 2004;Wallace, 2000Wallace, , 2005Wallace, , 2006Wallace et al, 2004Wallace et al, , 2008Hoek et al, 2008). A number of studies of exposures while driving have been done (Westerdahl et al, 2005;Fruin et al, 2008;Zhu et al, 2008).…”
mentioning
confidence: 99%